Improving Soil Quality and Yield of Intercropping-System Crops in a Dry Land Area through Plant Growth Promoting Rhizobacteria Application Frequency - Ida Ekawati; Henny Diana Wati; Maharani Pertiwi Koentjoro; Herni Sudarwati; Praptiningsih Gamawati Adinurani; Roy Hendroko Setyobudi; Rizal Andi Syabana; Rusli Tonda; Shazma Anwar (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2024)
The future of agriculture is prone to choose technology that can enhance the quality of the resources to support the sustainability of food production. Plant Growth Promoting Rhizobacteria (PGPR) is a reliable technology for future agriculture as it is environment-friendly, and able to optimize resource utilization and decrease external input. This research aimed to analyze the effect of PGPR (Pseudomonas fluorescens + Bacillus polymyxa) application frequency on chemical soil properties, a yield of an intercropping system in dry land, the in-between correlation of the parameters, and to determine the best PGPR application frequency. Randomized Complete Block Design (RCBD) was used in this research to put the treatment in the experimental unit properly. The treatments consisted of i) one-time application of PGPR at the planting time, ii) twice application of PGPR at the planting time and 15 Days After Planting (DAP), iii) three times application of PGPR at the planting time, 15 DAP and 30 DAP, iv) without application of PGPR as control. The results showed that PGPR application frequency improved chemical soil properties, yield, and total by-products as livestock feed. The activity of soil enzymes, nitrogenase, and phosphatase, was enhanced compared to the control. The application of PGPR in dryland areas is recommended to maintain soil fertility and support sustainable intercropping crop production. Further studies are needed to conduct mixed farming between agriculture, animal husbandry, clean energy (biogas), and organic fertilizer (residue from the biogas digester).